Weed Management in Root and Tuber Crops in India: Critical Analysis - Maniyam, Nedunchezhiyan; CS, Ravindran; Velumani, Ravi (JOURNAL OF ROOT CROPS, 2014)
Weeds are ubiquitous and continue to be an important constraint in the production of root and tuber crops owing to the initial slow growth of these crops. In India, weeding is predominantly done by the use of manual labour and to a limited extent through mechanical means. Weeding consumes about 30% of the total labour input and about 150-200 man days ha-1. The implementation of National Rural Employment Guarantee Scheme of Government of India has seriously affected the availability of labour for agricultural operations. The draught animals which were commonly used for intercultural operations in cassava along with gorru (7 tynes/9 tynes) in Andhra Pradesh are slowly but steadily making an exit because of high maintenance cost. Farmers are beginning to think of alternatives and herbicides are the obvious choice for many. Research results revealed that the pre-emergence herbicides, oxyflourfen, alachlor, butachlor etc. and the post-emergence herbicides, paraquat and glyphosate in combination with hand weeding was effective in weed control of cassava in various agro-climatic conditions of India. Pre-emergence application of isoproturon @ 1.0 kg ha-1 was found effective in taro weed management. In elephant foot yam, straw mulching, pre-emergence herbicide oxyflourfen and post-emergence herbicide glyphosate were effective for weed control. The use of herbicides is expected to grow further in the near future due to non availability of labours and draught animals for weeding. However, negative effect of herbicides on soil microbial population and starch concentration in cassava and other root and tuber crops was reported in certain locations. Mulching using weed control ground cover and diesel operated power weeder are highly suitable for weeding in widely spaced root and tuber crops. Hence, depending upon agro-ecosystem and socio-economic conditions, farmers can opt for any combination of weed control methods for effective management of weeds in root and tuber crops.